Modeling of perovskite solar cells - Zhantuarov, S.R.; Zholdybaev, K.S.; Aldiyarov, A.U.; Muchamedshina, D.M.; Tokmoldin, N.S.; Carnie, M.J. (Recent Contributions to Physics, 2018)
Perovskite materials, such as for example lead-halide methyl-ammonium perovskites, have proved to be a promising material for photovoltaics, thanks to their efficiency indexes. Using AFORS-HET-1D program a solar cell was modeled on the basis of the above-named material, operational parameters such as current-voltage characteristics, quantum efficiency, efficiency coefficient were obtained and analyzed. In addition, optimizing the model of the solar cell has been carried out along the thicknesses of the functional layers, the most efficient structure has been found in terms of efficiency coefficient. The solar cell model is close to its real counterparts in terms of efficiency indicators. Keywords: perovskite, solar cells, modeling, AFORS-HET-1D program, photovoltaics, promising material.